Antimicrobial And Antioxidant Activities Of Orthosiphon Stamineus Benth. With Emphasis On Rosmarinic Acid Content - Ho , Chun Hoong (2011)
Orthosiphon stamineus Benth. is a commonly planted herbal plant and is easily available in Malaysia. This herb is used in traditional medicine to treat a wide range of diseases. In this research, five types of O. stamineus extracts obtained through different ratios of analytical grade methanol (0, 25, 50, 75 and 100 %) and distilled water were tested against nine strains of food-borne bacteria in vitro using disc diffusion assay. From this assay, V. parahaemolyticus was found to be the most susceptible bacteria.